Reconstructing the Eco-Pedagogical Paradigm in Islamic Education through Tafsir Tarbawi of Surah al-Baqarah (2):30 - Susetyo, Marwal Blantara; Surahman, Cucu; Sumarna, Elan; Husaeni, Muhammad Fahri Ali; Dzakiya, Mifta Ghina (TAFSE: Journal of Qur'anic Studies, 2025)
This study reconstructs an eco-pedagogical paradigm in Islamic Religious Education by analysing the tafsīr tarbawī interpretation of Surah al-Baqarah (2):30. Existing discussions on Islamic environmental ethics often remain normative and philosophical, with limited attention to how Qur’anic ecological values can be operationalised into curriculum components and measurable learning practices. Using qualitative library research, this article compares five exegetical works that represent diverse styles and periods, namely Ibn Kathīr, al-Qurṭubī, al-Marāghī, al-Mīzān, and al-Miṣbāḥ. Data were analysed through content analysis by identifying key concepts in the verse, mapping convergences and variations across interpretations, and translating the results into curriculum elements, including learning objectives, materials, and assessment. The findings show a shift in the meaning of khalīfah from political legitimacy in classical readings to a broader cosmic mandate of environmental stewardship in contemporary interpretations. The angels’ concern about fasād and bloodshed functions as a pedagogical warning that supports the internalisation of three curricular pillars: tawḥīd, amānah, and mīzān. Based on these pillars, the article proposes a curriculum integration matrix across educational levels and an evaluation rubric for ecological piety that covers cognitive, affective, and psychomotor domains.